The mechanism of substructure formation and grain growth 316L stainless steel by selective laser melting. (8th September 2021) - Yang, Dengcui; Yin, Yanjun; Kan, Xinfeng; Zhao, Yan; Zhao, Zhengzhi; Sun, Jiquan
Abstract: This paper aims to investigate the unique substructure and grain growth of 316L stainless steel processed by selective laser melting (SLM) and clarify the mechanism. Results showed that the grain orientation on the x-z plane parallel to the build direction was the same type as the y-z plane, which all grow along the heat flow direction to form elongated columnar grains passing through the multi-layer fusion line. The epitaxial growth direction of grains changed abruptly with the vary of temperature gradient direction. Moreover, to expound the substructure formation based on solidification theory, a finite element model was established to obtain the distribution map of cooling rate G × R and solidified morphology G/R.